Analisis Faktor yang Mempengaruhi Terjadinya Tindak Pidana Ekonomi: Studi pada Tindak Pidana Korupsi di Indonesia - Vannya Quinta Husin; Fristia Berdian Tamza; Ahmad Irzal Fardiansyah (CV Rewang Rencang, 2025)
Corruption is one of the very serious problems that almost every country in the world, including Indonesia, is currently facing. This crime not only harms the country's finances but also disrupts social relationships and governance, hinders national development, and undermines public trust in the government. This study aims to discuss and examine the factors that cause the occurrence of corruption crimes in Indonesia. This research uses a literature study method that refers to books, scientific journals, legislation, and relevant documentation data. The literature analyzed in this study employs a descriptive qualitative approach to comprehensively understand the factors and aspects that are the reasons and causes of corruption crimes in Indonesia. There are four aspects that contribute to the occurrence of corruption crime in Indonesia, and it is very difficult to address this issue without a strong and collective commitment to eradicate it. The aspects are: Political Aspect, Legal Aspect, Economic Aspect, and Institutional or Organizational Aspect. All of these aspects are closely interconnected, making it necessary to have solid synergy to eliminate corruption at its roots and achieve the aspirations desired by all Indonesian people.